Reification of space within knowledge production: the case of the circulating idea of resilience internationally and in the context of South African cities - Ntamack, Serge (My University, 2017)
In this thesis, elements of Crawford Stanley Holing's life history are put into perspective. It provides a historical trajectory upon which the space imbued in the various contexts hosting pivotal activities on the production and refinement pf resilience idea are explored. These elements are also used as a point of departure from where the idea of resilience originates and circulates internationally and in the context of South African cities. [Abbreviated abstract. Open document to view full version]
Thesis is submitted in partial fulfilment for the degree of Doctor of Philosophy to the Faculty of Engineering and the Built Environment, School of Architecture and Planning, at the University of the Witwatersrand, Johannesburg, 2017
Keywords: City planning--South Africa; Public spaces--South Africa; Spatial behavior